THE NEW PARADIGM OF THE STATE CIVIL APPARATUS AFTER RATIFICATION OF THE STATE CIVIL SERVICES REGULATION - Dita Mayreista (STIH Putri Maharaja, 2021)
The main role and resposiblity of bureaucracy is to organize the nation and state constitusionally, it needs to be realized that the bureaucracy is a factor that determines the success or failure of a government. So far, the bureaucracy is still considered convoluted and the widespread practice of KKN (Corruption, Collusion and Nepotism; not only makes bureaucratic services access very difficult for the public, but also makes people have to pay more in terms of services and human resource who are slow in providing service. This study aims to determine how the New Paradigm of State Civil Apparatus after the ratification of the State Civil Apparatus Law. This research is qualitative descriptive study. The formation of the ASN Law is the beginning of the management of ASN which is expected to be more professional, transparent and accountable bureaucracy because ASN is a major factor in state administration. The existence of the “Merit” system and the profesionality of ASN (civil servant) support in providing excellent public services. And with the existence of KASN, it is expected to be able in managing, monitoring, and evaluating of ASN policies and management implementation.